ANALISIS SISTEM INFORMASI AKUNTANSI PENDAPATAN PELAYANAN RAWAT JALAN DALAM MENINGKATKAN PENGENDALIAN INTERNAL PENDAPATAN PADA RUMAH SAKIT DIRGAHAYU SAMARINDA - Koten, Kristina Lepan (EKONOMIA, 2018)
The purpose of the research is analyzing and discovering the accounting information system of outpatient services income in Dirgahayu Hospital Samarinda and comparing it with the internal control income system according to Mulyadi's theory. This research focuses on information systems of accounting income which is applied to the outpatient services of Dirgahayu Hospital. The importance of this research is the activities of outpatient services income which have a high risk of unaccountability if there is no accounting information system and the proper internal control income.The analysis tool of the research is Comparative Analysis which is an analysis to compare the internal control income system according to Mulyadi’s Theory with the internal control income system of Dirgahayu Hospital Samarinda through the accounting information system of outpatient services. It is done by compatibility test with the calculation of relative value by using the Dean J. Champion’s formulaThe result of the research shows that the accounting information system of outpatient income of Dirgahayu Hospital Samarinda with the income control system according to Mulyadi's theory is equivalent with relative value 95% with the category "Very Appropriate " so that the hypothesis of the research is accepted because the accounting information system of outpatient income in Dirgahayu Hospital has been done in accordance with the elements of internal control income according to Mulyadi's theoryBased on the results of the research, it can be concluded that the accounting information system of outpatient income of Dirgahayu Hospital Samarinda is suitable with elements of internal control income based on studies and theories. .